Revisiting Ibn Rushd's Demonstrative Philosophy: Bridging Classical Thought and Scientific Integration in Contemporary Islamic Higher Education - Muwaffiqillah, Moch.; Zulfa, Indana; al-Akiti, Muhammad Ayman (Tribakti: Jurnal Pemikiran Keislaman, 2025)
This article aims to examine the thoughts of Ibn Rushd, particularly regarding the concept of the relationship between Sharia (religion) and Hikmah (philosophy) through the principle of double truth, and to explore its potential as a philosophical foundation for the development of integrative knowledge in Islamic Religious Higher Education (PTKI). This study also seeks to address the stigma that views Ibn Rushd as being in opposition to Islamic orthodoxy as upheld by al-Ghazali. By employing a qualitative approach through content analysis of Ibn Rushd’s major works on demonstrative philosophy (burhani reasoning), this research explores the relevance of his thought in integrating religious and general sciences within PTKI. A contextual analysis is conducted to understand the challenges and opportunities for applying his philosophy in Indonesia, where it has received relatively little attention compared to the Western world. The findings indicate that Ibn Rushd’s demonstrative philosophy, which emphasizes demonstrative logic and empirical observation, offers a robust methodological framework to support the integration of knowledge within PTKI. The burhani approach can serve as an epistemological foundation that bridges the dichotomy between religious and general sciences while contributing to the development of a holistic curriculum. This study provides a theoretical contribution by reaffirming the relevance of Ibn Rushd’s thought in shaping a rational and empirical paradigm of Islamic higher education. Additionally, it opens a space for discussion on the role of Islamic philosophy in addressing the challenges of religious education in the modern era.